2011
DOI: 10.1016/j.jtcvs.2010.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with in-hospital mortality in infants undergoing heart transplantation in the United States

Abstract: Objective Infants undergoing heart transplantation have the highest early posttransplant mortality of any age group. We sought to determine the pretransplantation factors associated with in-hospital mortality in transplanted infants in the current era. Methods All infants under 12 months of age who underwent primary heart transplantation during a recent 10-year period (1999-2009) in the United States were identified using the Organ Procurement and Transplant Network database. Multivariable logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
2
24
1
Order By: Relevance
“…This finding was not reported in the PHTS report but is consistent with our previous work in other cohorts. 7,[19][20][21] Third, although black children remain at higher risk of posttransplant mortality, 1 we did not find any association of race/ethnicity with wait-list mortality. This finding is consistent with a recent report that showed that racial gaps, previously present in children awaiting HT in the United States, are absent in the current era.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding was not reported in the PHTS report but is consistent with our previous work in other cohorts. 7,[19][20][21] Third, although black children remain at higher risk of posttransplant mortality, 1 we did not find any association of race/ethnicity with wait-list mortality. This finding is consistent with a recent report that showed that racial gaps, previously present in children awaiting HT in the United States, are absent in the current era.…”
Section: Discussioncontrasting
confidence: 56%
“…Differences in pre-HT risk of graft loss could have played a role in graft outcomes between SF and MS groups; however, we found no difference in graft or patient survival based on MS use in multivariable analysis. Variables other than MS that we found to be independent risk factors for graft loss have been shown to be independent risk factors in previous studies (4)(5)(6)(7)(8), The results of our multivariable model were confirmed by our propensity-matched analysis, which similarly showed that there is no graft or patient survival advantage to the use of MS. Propensity-matched analysis did not show that induction therapy influenced outcomes or that a combination of induction therapy or no induction with or without MS use made a difference in graft outcomes, which is consistent with data from the International Society for Heart and Lung Transplantation registry (1). However, we did not differentiate between the type of induction agent used and it is not known whether any combination of a particular induction agent with an MS or SF regimen would affect graft outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…Re-entry of the thorax becomes increasingly challenging and hazardous with each prior sternotomy and is associated with a 4-fold elevation of in-hospital mortality (15). Adhesions, destabilising bleeding on resternotomy, and difficult cannulation may be encountered.…”
Section: Technical Considerationsmentioning
confidence: 99%